BASIC PRINCIPLES OF LABOR MARKET MANAGEMENT - Mamatkulov Tukhta Daminovich (Scholar Express Journals, 2023)
This article covers the main principles of labor market management. Theoretical views on the further improvement of the labor market in the regions are presented. Also, scientifically based proposals on implementation of economic methods, economic relations management mechanisms and management tools in the management of the labor market have been developed.
Keywords: labor market; population employment; employment